Pengaruh Pelatihan, Profesionalime Terhadap Penggunaan Aplikasi E-Procurement Siaplah Dimediasi Oleh Persepsi Kemudahan Pada SMP di Jawa Tengah - Fajarwati Sumardi Putri; Sangka Khresna B; Sabandi M (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to (1) determine the influence of training on the use of the e-procurement application SIPLah, (2) determine the influence of professionalism on the use of the e-procurement application SIPLah, (3) determine whether the perception ease of use can mediate the influence of training on the use of the e-procurement application SIPLah, and (4) determine whether the perception ease of use mediates the influence of professionalism on the use of the e-procurement application SIPLah in Junior High Schools in Central Java. This research was conducted quantitatively using path analysis with SEM-PLS. The population of this study comprises junior high schools that use the e-procurement application SIPLah, with a sample size of 392 schools in Central Java. The results of the study indicate that (1) Training has a significant effect on the use of the e-procurement application SIPLah with a p-value of 0,009, (2) Professionalism significantly affects the use of the e-procurement application SIPLah with a p-value of 0,008, (3) The perception of ease does not mediate the effect of training on the use of the e-procurement application SIPLah with a p-value of 0,075, and (4) The perception of ease significantly mediates the effect of professionalism on the use of the e-procurement application SIPLah with a p-value of 0,000.